Financial analysis and financial plan of Thyssenkrupp AG - Markova, Sofiia; Pham, Hoang Long; Marek, Petr; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
The financial analysis of Thyssenkrupp AG, a German industrial conglomerate, over the past six years of its performance.The theoretical and empirical parts focused on Financial Ratio Indicators, Vertical and Horizontal analyses, and a comparison with its Peer Group.Background of the strategic decisions: the scheduled separation of Thyssenkrupp Marine Systems and the segment‘s dissolution of Elevator Technology.Interpretation of the results for stock advice with a financial plan for 2025.
Vedoucí práce: Hoang Long Pham
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses